Utilization of Coffee Dregs into Charcoal Briquettes as a Circular Economy Solution for Energy Sustainability - Awalina, Mei; Meilani Fauziah Hasibuan, Ummi; Sari Lubis, Delima; Syahuri Zein, Aliman (Fakultas Ekonomi dan Bisnis Islam, 2025)
Coffee consumption and the number of coffee shops in Indonesia are increasing. The increase in the amount of coffee production and consumption must be accompanied by efforts to manage the resulting coffee grounds waste. In this study, coffee grounds, which often become waste, are processed into a high-value product, namely charcoal briquettes. This processing not only reduces the amount of waste generated, but also produces an energy source that is more environmentally friendly than fossil fuels. Briquetted charcoal can be used for various purposes, such as cooking and heating. The objective in this study is to analyze the benefits of the innovation of utilizing coffee grounds into briquetted charcoal that offers solutions in the context of a circular economy for energy sustainability.